Children's Oral Health Behavior in Cultural Practice: A Qualitative Study of Early Childhood Caries in Padang City - Pujiastuty, Arymbi; Effendi, Nursyirwan; Machmud, Rizanda; Astoeti, Tri Erri; Nurti, Yevita; Ramdesta, Andry; Fatasa, Uzika Putri; Ramadhan, Fajar (Universitas Padjadjaran, 2026)
Early Childhood Caries (ECC) remains a major public health concern in Indonesia. While global studies have widely applied the Health Belief Model (HBM) to explain parental perceptions of oral health, limited research has integrated local cultural values and the role of early childhood education (ECE) in shaping oral health practices. This study explores how cultural norms, parenting styles, and educational settings influence children’s oral health behaviors in Padang City.This study uses a qualitative case study design conducted at three early childhood education institutions with a Holistic Integrative Early Childhood Education program in Padang City (RA Ar Risalah, Adzkia, and Nirbas). Data was collected through observations, semi-structured interviews with parents and teachers and literature review. Purposive sampling identified actor informants (parents of children with and without caries) and ordinary informants (teachers, principals). Data analysis followed Miles and Huberman’s three-stage approach: coding, data display, and conclusion drawing. Findings show that toothbrushing is culturally embedded in bathing routines, maternal control over diet is stronger than paternal or extended family control, and dental care is largely perceived as curative rather than preventive. ECC in Padang City reflects a complex interplay of cultural practices, parental roles, socioeconomic conditions, and institutional support. Addressing ECC requires culturally grounded interventions that involve both family and PAUD educators, while reframing oral health as preventive rather than curative.